2015
DOI: 10.12659/msm.894554
|View full text |Cite
|
Sign up to set email alerts
|

MiR-29 Induces K562 Cell Apoptosis by Down-Regulating FoxM1

Abstract: BackgroundLeukemia seriously threatens human life and health. MicroRNAs can regulate cell growth, proliferation, and death. This article investigated the role of miR-29 on regulating leukemia cell growth, proliferation, and apoptosis.Material/MethodsmiR-29 and scramble miRNA were transfected to K562 cells. MTT assay, colony formation assay, caspase-3 activity detection, and flow cytometry were applied to test miR-29 effect on cell growth, proliferation, and apoptosis. Western blot was used to detect Forkhead b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…A literature examination of many of these differentially regulated miRNAs shed some light on their known roles, and many were found to contribute to the formation and/or function of the nervous system (Table 1). Many of these miRNAs also exhibited overlapping cellular functions, contributing to processes such as tumorigenesis [23][24][25][26][27][28][29][30], differentiation [31][32][33], proliferation [34][35][36][37][38], apoptosis [39][40][41][42], and cell cycle regulation [34,43,44]. A subset of the miRNAs was associated with nervous system-specific processes, such as differentiation [45][46][47][48][49], lifespan [50], neurite guidance [51][52][53], or synaptogenesis [54][55][56].…”
Section: Identification Of Mirnas That Were Differentially Regulated mentioning
confidence: 99%
“…A literature examination of many of these differentially regulated miRNAs shed some light on their known roles, and many were found to contribute to the formation and/or function of the nervous system (Table 1). Many of these miRNAs also exhibited overlapping cellular functions, contributing to processes such as tumorigenesis [23][24][25][26][27][28][29][30], differentiation [31][32][33], proliferation [34][35][36][37][38], apoptosis [39][40][41][42], and cell cycle regulation [34,43,44]. A subset of the miRNAs was associated with nervous system-specific processes, such as differentiation [45][46][47][48][49], lifespan [50], neurite guidance [51][52][53], or synaptogenesis [54][55][56].…”
Section: Identification Of Mirnas That Were Differentially Regulated mentioning
confidence: 99%
“…VSMCs constitute the majority of the blood vessel wall (43) and their growth or programmed cell apoptosis serves an important role in the altered geometry of vessels in vascular diseases, thus promoting the rupture of aneurysms. Accordingly, VSMC apoptosis was utilized as an in vitro model of IA (35). Results from the present study demonstrated that miR-29a inhibition attenuated the apoptosis of HBVSMCs; whereas, miR-29a overexpression increased HBVSMC apoptosis.…”
Section: Discussionmentioning
confidence: 58%
“…Previous studies have demonstrated that miR-29a is able to induce cell apoptosis by activating caspase proteins (33,34). For example, miR-29a was reported to be responsible for the activation of caspase-3-induced K562 cell apoptosis (35). Therefore, miR-29a was selected for further investigation in the present study.…”
Section: Resultsmentioning
confidence: 96%
“…A single miRNA can take part in the different biological process by regulating the expression of its target genes (Wei et al, 2013; Wang et al, 2015; Cui et al, 2016). Based on previous studies, miR-10a was reported to be involved in collagen type I generation of hypertrophic scars, embryonic cardiac development, type 2 diabetes mellitus and chronic myeloid leukemia CD34 + cells, etc.…”
Section: Discussionmentioning
confidence: 99%